Role of foliar fungal endophytes in litter decomposition among species and population origins - Gundel, Pedro Emilio (2016)
Litter decomposition is a key ecosystem process which returns nutrients from dead plant material to mineral forms in the soil. We examined whether systemic fungal endophytes modulate recycling of nutrients directly by altering litter decomposition. We studied litter decomposition mediated by Epichloë endophytes in litter-bag experiments. We examined direct endophyte effects on litter decomposition in wild populations and cultivars of Schedonorus phoenix and Schedonorus pratensis. In the first experiment, endophyte presence tended to increase litter decomposition rate in cultivars of the two grass species (S. phoenix and S. pratensis). However, in the second experiment plant origin had a stronger influence than endophyte symbiosis in S. phoenix. Interestingly, the initial level of alkaloids was associated positively with decomposition in S. phoenix populations. Characteristics associated with litter quality were not clearly related to either endophytes or decomposition rate. Our results suggest that endophytes can enhance litter breakdown but their role in nutrient cycling is far more complex depending on plant population origin.